Hak Atas Kekayaan Intelektual (HAKI) - Andi Candra; Warmiyana Zairi Absi; Sudarna (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2023)
Every work that is born from brilliant ideas useful for humans needs to be recognized and protected by the Indonesian government. For this reason, the Intellectual Property Rightssystem is needed as a form of appreciation for the work. In addition, the Intellectual Property Rights system supports the establishment of a good documentation system for all forms of human creativity, so that the possibility of producing the same technology and works can be avoided or prevented. The existence of legislation that regulates the Intellectual Property Rights, the community can work optimally for the necessities of life or develop it further to provide even higher added value.